Menggunakan Perspektif Feminis Post- Structualisme : Analisis Gender melalui Bermain Anjang-anjangan di Pendidikan Anak Usia Dini - Ramdaeni, Suci (IAIN Syekh Nurjati Cirebon, 2024)
This study explores how forms of femininity in Sundanese culture are constructed through playing anjang-anjangan for girls. Through a post-structuralist feminist approach, this study attempts to explore how children in Early Childhood Education continue to produce forms of femininity through playing anjang-anjangan to strengthen the differences between boys and girls in PAUD. This study uses an ethnographic focus that was conducted for approximately 2 months. The results of this study indicate that the construction of forms of femininity through playing anjang-anjangan often harms girls and boys. Playing anjang-anjangan is very gendered, where girls have more opportunities to play anjang-anjangan, in contrast to boys. Especially boys who are interested in playing anjang-anjangan are often not given the opportunity or are treated as othered. This finding is expected to be a reflection for teachers and adults in Early Childhood Education that playing is a child's right for both girls and boys without exception playing anjang-anjangan.